The impact of financial risks on bank performance: evidence from Bayesian analysis in Vietnam's commercial banks - Huyen Khanh Ngo; Hang Thi Thu Trinh (Discover Sustainability)
Abstract This research examines how financial risks influence the performance of Vietnam’s ten largest joint-stock commercial banks, with return on equity as the primary profitability metric. Spanning the years 2015 to 2023, the study applies a Bayesian regression model to ensure a robust and thorough analysis. The data includes audited annual financial statements from the selected banks. At the same time, macroeconomic indicators such as GDP growth and inflation are sourced from the SBV and WB. This study explores the critical financial risks that affect bank performance, focusing on credit, liquidity, and operational risks. It also considers the impact of bank size, GDP growth, and inflation rate on bank performance. The analysis shows a clear negative impact of these financial risks on bank profitability, as higher credit and operational risks are associated with reduced financial performance. This underscores the critical importance of financial risk management in effectively monitoring and controlling key performance indicators in joint-stock commercial banks. Moreover, both macroeconomic conditions and bank-specific attributes are shown to impact financial outcomes significantly. By offering insightful perspectives on risk management strategies, this study provides practical recommendations to enhance financial stability and bolster the resilience of Vietnamese commercial banks in an evolving economic landscape.